Distributional Pattern and Seasonal Changes of Gonadotrophs in the Hypophysis of Indian River Shad [Gudusia chapra (Hamilton, 1822)] in Relation to Ovarian Maturity - Barun, Shrabani (Contemporary Research and Perspectives in Biological Science Vol. 2, 2024)
The present study aimed to determine the seasonal environmental influence on the cytology of the pituitary gonadotrophs in relation to the gonadal maturation of clupeid fish Gudusia chapra by using various modern staining techniques. Reproduction performs under the influence of various external factors. It intervenes in their effect through the hypothalamo-hypophyseal-gonadal subsystem. It operates as an organic axis bridging the ecological influences and gonadal maturation. The function of the pituitary is mostly controlled by the hypothalamus through the synthesis and release of GnRH, therefore, acting as a major initiation of the hormonal cascade controlling the reproductive axis. Information is collected through the hypothalamus and is passed on to the hypophysis. The hypothalamus releases the Gonadotropic releasing hormone (GnRH) which exerts its effect on the hypophysis/pituitary to release gonadotrophin hormone from gonadotrophs of the Pituitary. The gonadotrophic hormone helps in gonadal maturation and sex steroid production which plays a very important role in oogenesis, the final maturation of oocytes. The Pituitary gland of G. chapra is cranio-leptobasic type. It is generally composed of neurohypophysis and adenohypophysis. The adenohypophysis is divided into three parts viz., rostral pars distalis (RPD), middle proximal pars distalis (PPD) and massive pars intermedia (PI). The major part of the RPD is occupied by the acidophilic prolactin cells (PRL) stained with acid fuchsin. Fewer adrenocorticotropic cells (ACTH) were scattered among prolactin cells. The basophilic gonadotrophs (GTH) and thyrotrophs (TSH) reacted positively to aniline blue and periodic acid Schiff’s (PAS) were distributed in the anterior and middle part of PPD. The neurohypophysis in G. chapra is composed of axonal nerve fibres originating from neuronal cell bodies of the hypothalamus. These nerve fibres extend as narrow strips into the pituitary gland and are found to be closely associated with the blood vessels. The somatotrophs (STH) were the only acidophils that were identified. Melanocyte stimulating hormone (MSH) stained with aniline blue and melanocyte concentrating hormone (MCH) stained with acid fuchsin were identified in PI. During the growth and maturation phase, both GTH and TSH cells were distinguished by intense staining and dense homogenous granules with maximum cellular diameter. During the post-spawning phase, both cells showed low staining intensity. The seasonal changes in the ovary of G. chapra have been described on the basis of variation in the Gonado-somatic index (GSI value) and frequency percentage of the different female germ cells. The gradual change in the ovarian cycle has been correlated with changes in GTH and TSH cells in the pituitary of Gudusia chapra. These studies would help to ascertain the proper maturity stages of gonads and the knowledge of control mechanisms of reproduction and these findings can be manipulated to accelerate or delay oogenesis in brood fishes.